Recent structural insights into the function of copper nitrite reductases. Issue 11 (12th July 2017) - Horrell, Sam; Kekilli, Demet; Strange, Richard W.; Hough, Michael A.
Abstract : Copper nitrite reductases (CuNiRs) catalyse the reduction of nitrite to nitric oxide as part of the denitrification pathway. In this review, we describe insights into CuNiR function from structural studies. Abstract : Copper nitrite reductases (CuNiR) carry out the first committed step of the denitrification pathway of the global nitrogen cycle, the reduction of nitrite (NO2 − ) to nitric oxide (NO). As such, they are of major agronomic and environmental importance. CuNiRs occur primarily in denitrifying soil bacteria which carry out the overall reduction of nitrate to dinitrogen. In this article, we review the insights gained into copper nitrite reductase (CuNiR) function from three dimensional structures. We particularly focus on developments over the last decade, including insights from serial femtosecond crystallography using X-ray free electron lasers (XFELs) and from the recently discovered 3-domain CuNiRs.